Geochemistry and genesis of thin-layered gabbroids of the Peterman Island (West Antarctica) - Artemenko, G.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
In the intrusion of gabbroids of the Andean complex on the Peterman island (West Antarctica), a xenolith (3×8 m) of thin-layered gabbro, in which there is an alternation of strips 3 cm wide of gabbroids with dif fe rent amounts of dark-colored minerals, is revealed. The origin of this stratification is explained by the sorting of crystal nuclei during the laminar flow of the melt in the inlet channel of a still hot intrusion that underwent the rapid bulk crystallization. In terms of chemical composition, thin-layered gabbro do not differ from containing uniform gabbros. Gabbroids of the Piterman island were formed from a high temperature plume melt. They are charac terized by a low content of silica and potassium. The main magma source for them was the PM mantle. Gabbroids are contaminated with a core material, as indicated by the low ratio (Nb/La)N = (0.22-0.86). This contamination is probably due to the regressive metamorphism of gabbroids caused by the introduction of later intrusions of granitoids of the Andean complex. The xenolith of thin-layered gabbro is probably a fragment of one of the supply channels for the final intrusive phases of the gabbroid massif.